A multiplex dual-probe RT-LAMP assay for rapid subtype-specific detection of respiratory syncytial virus A and B - Min Sup Lim; Chansoo Park; Eunji Lee; Sun-Young Ko; Woong Sik Jang (PLoS ONE, 2026)
Respiratory syncytial virus (RSV) is a leading cause of acute respiratory tract infections, particularly in infants, older adults, and immunocompromised individuals. RSV is classified into two major subtypes, RSV A and RSV B, which co-circulate seasonally and exhibit genetic variability, highlighting the need for rapid and subtype-specific diagnostic methods. Although reverse transcription quantitative PCR (RT-qPCR) is the reference standard for RSV detection, its reliance on complex instrumentation limits its applicability in decentralized testing settings. In this study, we developed and evaluated a probe-based reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for rapid detection and differentiation of RSV A and RSV B. The assay incorporates a dual-probe strategy, employing an assimilating probe for RSV A detection to ensure robust signal generation under multiplex conditions, and hybridization-based TaqMan-style probes (HyTaq probes) for RSV B detection and for an internal control targeting the human ACTB gene to ensure reaction validity. Analytical performance was assessed using serially diluted RSV positive clinical specimens and plasmid standards. Clinical performance was evaluated using 91 RSV A positive specimens, 97 RSV B positive specimens, and 120 RSV negative specimens, as defined by the reference diagnosis. The RSV A and RSV B RT-LAMP assays demonstrated sensitivities of 92.31% and 98.97%, respectively, with a specificity of 100% for both targets. No cross-reactivity was observed with a panel of common respiratory viruses. These results indicate that the proposed dual-probe RT-LAMP assay provides a rapid and specific approach for subtype-specific RSV detection, with potential applicability in decentralized diagnostic settings pending further validation.